PRELIMINARY ASSESSMENT OF THE IMPACTS OF DEEP FOUNDATIONS AND LAND RECLAMATION ON GROUNDWATER FLOW IN A COASTAL AREA IN HONG KONG, CHINA - Jiao J.J.; Wang X.; Nandy S. (My University, 2006)
Many coastal areas have been intensively urbanized because people living and working on or near coastlines are increasing. Land reclamation from the sea and high-rise buildings are common approaches to satisfying the growing needs for more housing and other land use. Coastal areas are usually the ultimate discharge zones of groundwater systems. Using a coastal area in Hong Kong as a case study, this paper discusses the change in a groundwater system due to land reclamation and construction of building foundations in a coastal area. The upper part of the study area is in a nearly natural state, whereas the lower part is probably one of the most extensively developed areas in the world. It is evident that the groundwater flow system in this area has been changed over the last century. The piezometers in the transitional zone between the natural slopes and the urbanized areas indicate significant response to rainfall and obvious upward groundwater flow. To understand these piezometric responses to rainfall, a cross section is selected for detailed study using a two-dimensional multilayered numerical model. The parameters and structure of the aquifer system are calibrated by comparing the simulated and observed water levels. To reproduce the observed behavior of the groundwater system, the model has to include two important characteristics: a highly permeable zone at the rockhead and a reduction in hydraulic conductivity of 14–20 times in the urbanized area. The simulation demonstrates that both land reclamation along the coastline and deep foundations have contributed to the modification of the flow system, but the deep foundations have the most profound impact, especially when a high conductivity zone is present at the rockhead.
Keywords: HYDRAULIC CONDUCTIVITY; GROUNDWATER FLOW; LAND RECLAMATION; MATRIC SUCTION; SUBMARINE GROUNDWATER DISCHARGE